Andarilhagens pelo mundo: Paulo Freire no Conselho Mundial de Igrejas - CMI - Ribeiro, Mario Bueno (2009)
In the actually economic models where sometimes profit it´s the aim ambition of some groups of people. All of the socials engagement centers has been usually subordinate to keep safe all of minority´s privileges which is supported by endless majority´s oppression. Since the XV century, a massive policy, called by colonialism has been established by iberic countries over crowed of people. This policy received an official seal of Church which had the responsibility to administrate international rights and used to concede occupation s permission. As a consequence; in this areas, it were created colonial mentality. Thought independent, colonies have been keeping this kind thought witch must to be changed, reason why oppressed people judge themselves not able to face this situation, this group of people have been fed by religious determinism. This work treats to Paulo Freire´s trajectory in part to World Council of Churches (WCC). Both of them were born in the XX century. Paulo Freire it´s a person, WCC it´s an International Found. Both efforts are common, it means: to contribute with Missio Dei seeking freedom of human person. The first one helps with his epistemological praxis and the second one with the financial support and both with humanities desires of freedom. The Paulo Freire´s trajectory in Brazil, Chile and USA it´s seemed in the chapter one and second one talks about the WCC. The chapter three it´s reserved to broach Paulo Freire´s trajectory from WCC. This work also offers us itinerary readings. It´s just contributions to keep in evidence all of Hope´s walkers ideals whose represents conscietization in the first sight e finally followed by freedom and human emancipation.